Bodies Bound for Circumcision and Baptism: An Intersex Critique and the Interpretation of Galatians - Marchal, Joseph A. 1974- (2010)
Arguments about the meaning of specific forms of embodiment resonate across a range of contexts, both theological and supposedly non-theological, ancient and contemporary. These forms are potently reconsidered in light of the modern medicalized management of intersex populations and the intersex critique in response to such management. Such a critique entails a new kind of accountability for biblical literature and interpretation, particularly as they inhabit an especially contested domain for claims about "nature" and belonging. The aim of this project, then, is to reflect upon the utility of biblical argumentation for an intersex critique, but also to demonstrate how attention to this critique challenges biblical interpretation, as it offers a new approach to religious argumentation about bodies, like Paul's in his letter to the Galatians. The ancient author and community's approaches to practices like circumcision and baptism reveal different conceptualizations of ostensibly ambiguous bodies and their anatomies of belonging, or "member"-ship.
Keywords: queer approaches; Pauline Letters; Intersex; Galatians; Circumcision; Baptism